2016
DOI: 10.1002/ece3.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Quaternary evolutionary history, potential distribution dynamics, and conservation implications for a Qinghai–Tibet Plateau endemic herbaceous perennial, Anisodus tanguticus (Solanaceae)

Abstract: Various hypotheses have been proposed about the Quaternary evolutionary history of plant species on the Qinghai–Tibet Plateau (QTP), yet only a handful of studies have considered both population genetics and ecological niche context. In this study, we proposed and compared climate refugia hypotheses based on the phylogeographic pattern of Anisodus tanguticus (three plastid DNA fragments and nuclear internal transcribed spacer regions from 32 populations) and present and past species distribution models (SDMs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 106 publications
(214 reference statements)
2
31
0
Order By: Relevance
“…In comparison with Europe and North America, the genetic structure and variation in Quaternary phylogeographic histories of plant species are much more pronounced in topographically complex regions of China, such as the Qinghai-Tibet Plateau (QTP) (e.g. Zhang et al, 2005;Meng et al, 2007;Wang et al, 2009aWang et al, , 2014Opgenoorth et al, 2010;Xu et al, 2010;Qiu et al, 2011;Zou et al, 2012;Wen et al, 2014;Liu et al, 2015;Zhang et al, 2015;Wan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison with Europe and North America, the genetic structure and variation in Quaternary phylogeographic histories of plant species are much more pronounced in topographically complex regions of China, such as the Qinghai-Tibet Plateau (QTP) (e.g. Zhang et al, 2005;Meng et al, 2007;Wang et al, 2009aWang et al, , 2014Opgenoorth et al, 2010;Xu et al, 2010;Qiu et al, 2011;Zou et al, 2012;Wen et al, 2014;Liu et al, 2015;Zhang et al, 2015;Wan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown evidence for the importance of Quaternary climatic oscillations in explaining genetic variability, distributions and demographic patterns observed in modern populations of QTP species (Tang & Shen, 1996;Bawa et al, 2010;Jia et al, 2011;Liu et al, 2012Liu et al, , 2014bLiu et al, , 2015Wan et al, 2016). In particular, many alpine species retreated to eastern or south-eastern refugia during glacial periods and recolonized the central plateau platform during the interglacial or postglacial stages (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These environments provide an ideal natural laboratory for studies on adaptive evolution. Organisms that live in the QTP must have undergone a series of significant adaptive evolutionary genetic changes to produce a wide range of ecologically adaptive characters [51,52]. Cyanobacteria can exist symbiotically in corals [53], and genome and transcriptome sequencing of cyanobacteria Trichormus sp.…”
Section: Can We Learn From the Adaptation And Evolution Of Other Ecosmentioning
confidence: 99%